Dialectics of complexity, emergence and management - Efremov, Victor; Vladimirova, Irina; Kolganova, Elena (Serbian Journal of Management, 2023)
The article is devoted to the dialectical analysis of such fundamental essences of modern organizations as complexity, emergence and management. It considers approaches to the quantitative assessment of complexity as a constructive feature of the system, while drawing attention to the fact that complexity is a direct result of the development of the system’s ability to adapt. The appearance of emergent properties in an organization is accompanied by an inevitable increase in its complexity. This growth should be controlled and regulated, and the level of emergence of the organization should correspond to the complexity of the environment. The more uncertainty needs to be eliminated, the more complex the organizational system becomes. From the authors’ point of view, the dialectic of entropy, complexity and emergence is as follows – strengthening the emergent properties of a set of elements requires minimizing entropy. In its turn minimizing entropy requires purposeful restriction of the freedom of system elements behaviour, which is provided by embedding into the system of managing elements and organizing the necessary set of connections, and that leads to an increase in the complexity of the organization.